2020
DOI: 10.3390/molecules25194463
|View full text |Cite
|
Sign up to set email alerts
|

Benzophenone and Benzoylphloroglucinol Derivatives from Hypericum sampsonii with Anti-Inflammatory Mechanism of Otogirinin A

Abstract: Three new compounds, 4-geranyloxy-2-hydroxy-6-isoprenyloxybenzophenone (1), hypericumone A (2) and hypericumone B (3), were obtained from the aerial parts of Hypericum sampsonii, along with six known compounds (4–9). The structures of these compounds were determined through spectroscopic and MS analyses. Hypericumone A (2), sampsonione J (8) and otogirinin A (9) exhibited potent inhibition (IC50 values ≤ 40.32 μM) against lipopolysaccharide (LPS)-induced nitric oxide (NO) generation. Otogirinin A (9) possessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Western blot analysis was performed according to the method previously reported [ 34 ]. In brief, A549 (1 × 10 5 cells) was seeded into 6 wells plate and grown until 85–90% confluent.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed according to the method previously reported [ 34 ]. In brief, A549 (1 × 10 5 cells) was seeded into 6 wells plate and grown until 85–90% confluent.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed according to the method previously reported [ 25 , 26 ]. Briefly, A549 and MCF-7 (1 × 10 5 cells) were seeded into 6-wells plate and grown until 85–90% confluent.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in this study the brasilixanthone B has been isolated and identified in H. perforatum for the first time [ 295 ]. Strengthening the defensive role of xanthones, Huang and collaborators in H. sampsonii [ 178 , 296 ] showed that cDNAs encoding HsBPS and HsCHS were differentially regulated in the vegetative and in reproductive stages. In the vegetative stage, HsBPS was highly expressed in the roots; its transcript level was approximately 100 times higher than that of HsCHS, whereas the young leaves contained higher transcript levels of HsCHS.…”
Section: Organ and Tissue Localization Of Xanthones And Their Possibl...mentioning
confidence: 99%